Japanese fabric flowers : 65 decorative kanzashi flowers to make - Blondeau, Sylvie (Search Press, 2015)
"The Japanese word kanzashi originally referred to decorative pins as part of the traditional female hairstyles. These pins were often works of art in themselves, holding in place elaborate floral arrangements made with natural or silk flowers. Today, kanzashi encompasses flowers made from regular fabrics. Sylvie Blondeau shows you how to make 65 of these simply stunning designs. The projects are so easy and fun to make that you will soon be making them for every occasion. Perfect as accessories on clothing, jewellery, home decorations or table adornments for special occasions." --